Exploratory analysis of driving behaviour to support the development of a discomfort indicator using a vehicle driving simulator - Silva, José Miguel Ribeiro da (2023)
Driver behaviour contributes significantly to road safety and environmental impacts. Therefore, a better understanding of how drivers react to different stimuli, such as road events and vehicle specifications, is fundamental in trying to minimise these adverse effects. Furthermore, an often-neglected component in the reference literature is the concept of comfort experienced by the driver and how it impacts the driving profile. Considering the global concerns of improving air quality, reducing emissions and increasing road safety, it is important to study and evaluate approaches to improve comfort and the driving/travelling experience. A useful tool in this area is the driving simulator, as it allows you to control the environment and scenarios based on real conditions without having the consequent risks of road and environmental conflicts that a test in a real environment would have. The main objective of this dissertation is to identify parameters related to driving behaviour that can contribute to the development of an indicator of comfort and travel experience. To achieve this goal, this research uses data collected from experiments conducted in a fixed driving simulator, in an urban scenario, involving different singularities. In this study, 30 volunteers underwent six simulations (three using an automatic transmission vehicle and three using a manual transmission vehicle) in an urban environment to obtain a significant sample considering the individual variability of each participant's driving behaviour. Throughout this simulation, several variables were collected on a second-by-second basis, such as speed, acceleration, and distance to the intersection, among others. From these variables, it was also possible to calculate driving volatility, which consists of the acceleration variation over time or jerk, the vehicle's specific power (VSP), and the VSP mode, which, in turn, provides the emission model used in this dissertation. Emission factors obtained from previous studies were used to estimate the instantaneous emissions resulting from the experiments. The simulator variables and the calculated ones were subsequently examined both in a general context and concerning specific road characteristics (e.g., a segment involving a speed bump and crosswalk, an intersection with a stop sign, an intersection with a yield sign, an intersection with a crosswalk, and finally an intersection with a traffic light). Specifically, a microscopic analysis was conducted along the area of influence of these events. As a result of this investigation, patterns were identified, and deviations were detected that allow the characterisation of driving behaviour in the studied events highlighting specific aspects that could be associated with assessing comfort. The overall results of the simulations allow to draw conclusions regarding the transmission modes, indicating a greater tendency for higher speeds and acceleration profiles in vehicles with automatic transmission compared to manual ones. In the study of the events, it was observed that for situations where the driver did not need to fully stop the vehicle had a lesser environmental impact, as seen in the case of yielding. On the other hand, events that may lead the driver to stop, such as traffic lights, pedestrian crossings, and mandatory stop intersections, cause jerk levels to increase, creating a greater sense of discomfort for the driver. In summary, we believe that the results obtained will be relevant to support decision- making regarding individual measures (e.g., transmission change indicators or controllers with sustainability objectives to minimise emissions and enhance comfort and safety) and policies (e.g., urban infrastructure planning strategies) to improve road safety as well as mitigate the environmental impacts intrinsic to driving tasks.